2018
DOI: 10.1016/j.trd.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Lift-share using mobile apps in tourism: The role of trust, sense of community and existing lift-share practices

Abstract: A B S T R A C TThis paper explores the use of mobile technology to enable lift-share in the leisure travel domain of camping tourism. Here mobile devices can connect a user community on the move undertaking non-routine trips and reveal temporal and spatial connections suggesting lift-share opportunities. Data were derived from a questionnaire survey (n = 339) administered at campsites in a rural tourism destination in Dorset, UK. Analysis focuses on the role of trust, sense of community and existing lift-share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Also, with the change in tourists' travel habits, the rate of mobile application usage and the popularity of the online travel market is increasing day by day (Jia, Li, & He, 2016). In particular, the ability of smartphones to be connected at any time to communicate with the world has made it easier for individuals to share with others while on the go and has made their travels more enjoyable through location-based services (Dickinson et al, 2018). For this reason, it is essential to explore the reasons for the use of technological applications.…”
Section: Technological Self-efficacymentioning
confidence: 99%
“…Also, with the change in tourists' travel habits, the rate of mobile application usage and the popularity of the online travel market is increasing day by day (Jia, Li, & He, 2016). In particular, the ability of smartphones to be connected at any time to communicate with the world has made it easier for individuals to share with others while on the go and has made their travels more enjoyable through location-based services (Dickinson et al, 2018). For this reason, it is essential to explore the reasons for the use of technological applications.…”
Section: Technological Self-efficacymentioning
confidence: 99%
“…Empirical studies have indicated that trust in online service providers surges customer's intention to use the service providers' website (Davari et al, 2022;Mukherjee et al, 2021;Dickinson et al, 2018;Morosan and DeFranco, 2015;Kaushik et al, 2015;Yap et al, 2010). For instance, Yap et al (2010) showed that trust in e-services positively affects the customers' willingness to adopt e-services.…”
Section: Willingness To Adopt the Websitementioning
confidence: 99%
“…Mobile connections also adopt new methods to connect with social networks, gradually integrating online and offline, and tourists can interact with the Internet across space and time [22]. This connection improves their chances of sharing in the user community of social networks [23] while extending travel to virtual spaces. The virtual reality and augmented reality (AR) devices that have been widely used in travel in recent years are mostly based on mobile technology [24].…”
Section: Tourism and Mobile Technologymentioning
confidence: 99%
“…Notably, among the top 13 authors, Dickinson, J. E., Cherrett, T., Davies, N., Norgate, S., and Speed, C. have a very close cooperative relationship. They studied the application or role of smartphone apps in travel [23,[40][41][42][43] and tourism social networks [22]. Wang, D. and Xiang, Z. also have a relatively stable cooperative relationship.…”
Section: Collaboration Network Analysismentioning
confidence: 99%